Effect of Water on the Viscosities and Densities of 1-Butyl-3-methylimidazolium Dicyanamide and 1-Butyl-3-methylimidazolium Tricyanomethane at Atmospheric Pressure - Carvalho, PJ (2010)
Despite the recent increase in the number of works addressing the effect of water on the thermophysical properties of ionic liquids (ILs), in particular densities and viscosities, the strong effect of the water content in the region of low water content on these properties requires further study for a deeper understanding of the phenomenon. Densities and viscosities of two imidazolium-based ionic liquids, 1-butyl-3-methylimidazolium dicyanamide [C(4)mim][N(CN)(2)] and 1-butyl-3-methylimidazolium tricyanomethane [C(4)mim][C(CN)(3)], and their binaries with water, for mole fractions up to 0.6, at atmospheric pressure and temperatures from (278.15 to 363.15) K were determined. The densities and viscosities of the pure ionic liquids and their binaries with water were described successfully by using several correlations. An extension to the Ye and Shreeve group contribution method shows a good agreement with the density data. An Orrick-Erbar-type approach and the Vogel-Tammann-Fulcher method were also applied to the experimental viscosity data, presenting a good agreement and allowing the estimation of new group contribution parameters, extending the applicability of these methods to new ILs. For mixtures, the one-constant Grunberg and Nissan equation was investigated for the correlation of the experimental viscosity binary mixture data of ILs + H(2)O, providing a good description of the experimental data using a single parameter for each ionic liquid studied.